1987
DOI: 10.1159/000124849
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coexisting Hypothalamic Messengers on Growth Hormone Secretion from Rat Anterior Pituitary Cells in vitro

Abstract: An increasing number of messengers have recently been found to coexist with growth hormone (GH)-releasing factor (GRF) in hypothalamic neurons. In view of a possible cosecretion of these substances with GRF into the portal circulation, the effect of synthetic rat hypothalamic GRF(1–43) alone, or together with dopamine (DA), L-dopa, γ-aminobutyric acid (GABA), neurotensin (NT) or galanin (GAL) on GH release was investigated by using dispersed rat anterior pituitary cells in monolayer culture. GRF in concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…Moreover, GH secretion induced by GHRH, GHRP, and PACAP from rat pituitary cells was inhibited by SRIF in vitro [11,23]. Furthermore, the inhibitory effect of SRIF on GHRH-induced GH secretion has been reported in in vitro studies in rats [2,24], in chickens [25], and also in vivo in young bulls [26]. The present study is in agreement with the demonstration that GHRP may be a useful probe to use in investigating the GH secretory mechanisms as reported by Badger et al [20], in their study on rat pituitary cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, GH secretion induced by GHRH, GHRP, and PACAP from rat pituitary cells was inhibited by SRIF in vitro [11,23]. Furthermore, the inhibitory effect of SRIF on GHRH-induced GH secretion has been reported in in vitro studies in rats [2,24], in chickens [25], and also in vivo in young bulls [26]. The present study is in agreement with the demonstration that GHRP may be a useful probe to use in investigating the GH secretory mechanisms as reported by Badger et al [20], in their study on rat pituitary cells.…”
Section: Discussionmentioning
confidence: 84%
“…These two hypothalamic peptides are released from nerve endings in the median eminence and reach the anterior pituitary via the hypophysial-portal circulation [1][2][3]. Moreover, it has been reported that GHRH and SRIF regulate mitotic activities of GH-producing cells and that the effect of GHRH is possibly mediated by cyclic AMP [4].…”
Section: Somatostatin Pituitary Cellmentioning
confidence: 99%
“…Several studies have shown that galanin administered to animals increases pituitary secretion of prolactin and GH (6)(7)(8)(9)(10)(11)). Galanin appears to mediate these effects at the hypothalamic level, and recent studies showed no direct effect of galanin on cultured pituitary cells (6,12,13). However, these studies used pGal and, therefore, do not exclude a direct effect of the homologous peptide on rat prolactin-and GH-producing cells.…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous pGal injection in humans stimulates GH release and augments the GH release induced by exogenous GH-releasing hormone (10, 11). pGal has little stimulatory effect on the release of these hormones in isolated pituitary preparations (6,(12)(13)(14), and there is evidence that its effects are exerted indirectly via the release of dopamine (for prolactin) and somatostatin (for GH) (8,11,15). Intracerebroventricular pGal increases luteinizing hormone release in ovariectomized rats treated with exogenous estrogen and progesterone (16).…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine also inhibits GH secretion from cultured pituitary cells, i.e. at the pituitary level (37,38). In contrast, the systemic administration of dopamine results in GH increment (27), probably due to the activation of hypothalamic hormones stimulating GH release.…”
Section: Journal Of Endocrinology (1999) 140mentioning
confidence: 99%